Characteristics of Grain Size Distribution on Beaches Sediment of Sumba Island, Nusa Tenggara Timur Based on Grainsize and Geochemical Data - Nugroho, Septriono Hari; Putra, Purna Sulastya (Pusat Survei Geologi, 2019)
Study of beaches sediment characteristics were conducted on three beaches on Sumba Island, East Nusa Tenggara.The research is a part of Widya Nusantara Expedition which conducted by using Research Vessel of Baruna Jaya VIII. The aim of this study is to determine the characteristics of coastal deposits through the observation of grain size by using the grain size trend analysis approach (Grain Size Trend Analysis, commonly abbreviated as GSTA) and geochemical analysis. A total of 36 samples were taken on each coast representing high tide, transition and low tide along the coast. A grain size analysis was performed using a Malvern Mastersizer 2000 that was processed with Gradistat 4.0 software. Geochemical analysis was carried out using X-ray fluorescence spectrometry (XRF). The distribution of beach sediments is dominated by moderate sand - coarse sand and differences on content of geochemical elements (Ca, Sr, Fe, K, and Ti). The coastal conditions that are connected to the Indian Ocean (B1) have different characteristics from the beach that connected to the Sumba strait (B5 and B7). GSTA analysis showed sediment of Laboya Beach finer than sediment on Waikelo and Melolo Beach. Geochemical elements on Laboya Beach indicates different values than others. It indicates there are differences in the provenance and composition of sediment on the all three beaches. The supply of coastal deposits on these three beaches is influenced by the mechanism of precipitation of the walls and the processes of waves and rivers.Keywords: distribution, sediment, grainsize, geochemical, XRF, beach sediment.